THE CHANGE OF SASHI’S SOCIAL IDENTITY IN ENGLISH VINGLISH MOVIE (2012) - Lifah, Halifah; Sili, Surya; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
English Vinglish (2012) is an Indian movie inspired from Gauri Shinde’s mother. This movie tells about a woman named Sashi who struggle for her social identity. This problem background encourages the researcher to analyze Sashi’s character and characterization and the change of her social identity. The researcher limits the focus of Sashi’s character and her social life. The researcher uses characterization theory and Social Identity Theory to conduct the analysis. The data are analyzed by using qualitative descriptive method. The findings of this research reveal that: Sashi is the main character in the movie, because she is given much contribution of the story. The characterization is about Sashi’s physical appearance, personality, social status and social relationship. Sashi’s physical appearance is, she is a beautiful woman with beautiful eyes, long black hair and white skin. Her personality shows that she is a patient woman, a loving person, has a high tolerance and a loyal person. Her social status is a woman with low education and not a modern woman. Sashi has relationships with other characters in this movie, good and bad relationships. The analysis about the change of Sashi’s social Identity is divided into two processes: self-categorization and social comparison. The researcher concludes that Sashi changes her social identity from an ordinary housewife who does not know English become well-educated woman who fluent in English. The researcher finds that to change Sashi’s social identity she has to pass self-categorization and social comparison.